Agricultural mechanization in Phnom Penh and Kandal Province of Cambodia - Seng Tuy; Salokhe, Vilas M.; Jayasuriya, H.P.W.; Athapol Noomhorm; Canillas, Emmanuel C.; Protected Cultivation Project; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2007)
This study is focused on studying the current status of agricultural mechanization in Phnom Penh Municipality and Kandal Province in Cambodia. Ninety households engaged in agricultural production from six villages were selected for personal interviews. On the other hand, three enterprises and nine selling shops of agricultural machinery and equipment, in Phnom Penh, were selected to contribute for this survey. During field survey included discussions with village and commune leaders, key informants, government officials, and farmers who had (or hired) cattle or power tiller or tractor. The study revealed that among the 90 respondents, 63 grew only rice, 3 grew vegetables only; and the other 24 grew rice and vegetable/subsidiary crop. About 33.3% of the respondents cultivated less than 1 ha of farm land, 46.7% cultivated 1-2 ha and 20% cultivated more than 2 ha. On the other hand, 15.6% of the respondents have less than 5 household members, 62.2% have 5-7 members and 22.2% have more than 8 members. The average plowing by a pair of draft animals is 40 man-hours/ha while power tiller takes 7.14-10 man-hours/ha and tractor takes 1-2 man-hours/ha. Labor cost is generally US$ 1.5-2.5/day/person (usually 1-2 meals are provided) while the method of labor exchange is still commonly practiced. The survey showed that the average rice yields of 2.72 t/ha and 4.88 t/ha in Khan Dangkor and Kien Svay districts respectively. Most farm machinery and equipment are imported and only some parts are locally produced. On the mechanization policy and strategies, SWOT analysis discussed the strengths, weaknesses, opportunities and threats concerning crop production in the study area. On the other hand, future trends of mechanization were also mentioned.
Thesis (M.Eng.) - Asian Institute of Technology, 2007
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Agricultural Systems & Engineering, School of Environment, Resources and Development
Keywords: Farm mechanization -- Cambodia